Musthafawiyahnomics: Community Socio-Economic Study - Atikah, Rahmi; Batubara, Maryam; Rahmani, Nur Ahmadi Bi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Musthafawiyahnomic is an Islamic boarding school that has become an icon of economic turnover because Musthafawiyah Islamic boarding school is one of the Islamic boarding schools whose students live side by side with society. This Islamic boarding school is also one of the Islamic boarding schools that has the biggest influence on the running of the economy in Mandailing Natal, especially Purba Baru village, such as local people, migrant traders, and outside communities. The role of the Musthafawiyah Islamic boarding school in improving the community's economy is by giving the community the freedom to rent out their land as a place for the students' cottages to stand, opening up opportunities to depend on their economy in the fields of trade, laundry, photocopying, barbershops, lodging, cottages, etc. Indirectly, Islamic boarding schools contribute to contact with society, to improve its welfare both from a socio-economic and religious spiritual perspective. This is in line with rural economics, namely development policies or strategies for the economic development of rural areas. The impacts of the existence of this Islamic boarding school are: firstly, there is social jealousy that arises between people who have businesses and those who do not because the location is less strategic. Second, the positive impact of the existence of the Musthafawiyah Islamic boarding school helps reduce unemployment in Purba Baru village, although it is not optimal, with the existence of this Islamic boarding school, unemployment in Purba Baru village can be reduced. The socioeconomic conditions of the community around the Mustafawiyah Islamic boarding school can be called Mustafawiyahnomic. This Mustafawiyah Islamic Boarding School is also an icon of society because the Musthafawiyah Islamic boarding school is one of the Islamic boarding schools whose students live side by side with the community. This Islamic boarding school is also one of the Islamic boarding schools that has the biggest influence on the running of the economy in Mandailing Natal, especially Purba Baru village, such as local people, migrant traders, and outside communities. This Islamic boarding school also has a big influence on the local community in the economic sector where the community makes this an opportunity to depend on their economy in the fields of trade, laundry, photocopying, hair trimming, lodging, cottages, etc.